NILAI-NILAI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN BAHASA ARAB PADA PEMBELAJARAN JARAK JAUH DI MADRASAH IBTIDAIYAH MIFTAHUL ULUM LEDOKOMBO - Syaiful Rizal (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2022)
Arabic teachers have challenges and roles in cultivating character education values ​​in learning Arabic in Distance Learning (PJJ) through social media and by instilling very, very important attitudes, namely the values ​​of faith and Islam such as. The purpose of this research is to find out the values ​​of character education in Arabic language learning and the challenges in PJJ in Class V of Madrasah Ibtidaiyah Miftahul Ulum Ledokombo. This research uses descriptive qualitative research. Sources of data in this study were Arabic Subject Teachers, Grade V MI-Miftahul Ulum Ledokombo Students, and Students' Parents. Data collection techniques using observation, interviews and documentation. While the data analysis technique used is the Miles, Huberman and Saldana model, in three ways, namely data reduction, data display, and verification. The results of the study show that character values ​​in learning Arabic at PJJ in Class V MI-Miftahul Ulum Ledokombo, can be seen from the cultivation of nine indicator character values, namely the character of love for God and all of His creation, independence and responsibility, honesty/trustworthiness. , diplomatic, respectful and courteous, generous, likes to help and cooperate, confident and hardworking, leadership and justice, kind and humble, character of tolerance, peace, and unity. The drawbacks are in the method, syllabus, lesson plans, and online networks, such as knowledge of existing technology / a little lack of understanding, lack of interaction between teachers and students so that children are less serious about learning, laziness in students and teachers rarely enter and the advantages are that the enthusiasm and hard work of the teachers and students is very good, many parents support or guide their children to study especially Arabic lessons, parental participation in guiding and advising children at home so that they can create positive character for children, as parents really helped shape my child's character, memorization and the existence of groups made us work together